Multi-ingredient pre-workout supplements, safety implications, and performance outcomes: a brief review - Patrick S. Harty; Hannah A. Zabriskie; Jacob L. Erickson; Paul E. Molling; Chad M. Kerksick; Andrew R. Jagim (Taylor & Francis Group, 2018)
In recent years, a new class of dietary supplements called multi-ingredient pre-workout supplements (MIPS) has increased in popularity. These supplements are intended to be taken prior to exercise and typically contain a blend of ingredients such as caffeine, creatine, beta-alanine, amino acids, and nitric oxide agents, the combination of which may elicit a synergistic effect on acute exercise performance and subsequent training adaptations compared to single ingredients alone. Therefore, the purpose of this article was to review the theoretical rationale and available scientific evidence assessing the potential ergogenic value of acute and chronic ingestion of MIPS, to address potential safety concerns surrounding MIPS supplementation, and to highlight potential areas for future research. Though direct comparisons between formulations of MIPS or between a MIPS and a single ingredient are challenging and often impossible due to the widespread use of "proprietary blends" that do not disclose specific amounts of ingredients in a given formulation, a substantial body of evidence suggests that the acute pre-exercise consumption of MIPS may positively influence muscular endurance and subjective mood, though mixed results have been reported regarding the acute effect of MIPS on force and power production. The chronic consumption of MIPS in conjunction with a periodized resistance training program appears to augment beneficial changes in body composition through increased lean mass accretion. However, the impact of long-term MIPS supplementation on force production, muscular endurance, aerobic performance, and subjective measures is less clear. MIPS ingestion appears to be relatively safe, though most studies that have assessed the safety of MIPS are relatively short (less than eight weeks) and thus more information is needed regarding the safety of long-term supplementation. As with any dietary supplement, the use of MIPS carries implications for the athlete, as many formulations may intentionally contain banned substances as ingredients or unintentionally as contaminants. We suggest that athletes thoroughly investigate the ingredients present in a given MIPS prior to consumption. In conclusion, it appears that multi-ingredient pre-workout supplements have promise as an ergogenic aid for active individuals, though further information is required regarding long-term efficacy and safety in a wider variety of populations.